2008
DOI: 10.5664/jcsm.27188
|View full text |Cite
|
Sign up to set email alerts
|

Increased Heart Rate Variability but Normal Resting Metabolic Rate in Hypocretin/Orexin-Deficient Human Narcolepsy

Abstract: Scientific inveStigAtionSStudy objectives: We investigated autonomic balance and resting metabolic rate to explore their possible involvement in obesity in hypocretin/orexin-deficient narcoleptic subjects. Methods: Resting metabolic rate (using indirect calorimetry) and variability in heart rate and blood pressure were determined in the fasted resting state. Subjects included 15 untreated, hypocretin-deficient male narcoleptics and 15 male controls matched for age and body mass index. Results: Spectral power a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 71 publications
(37 citation statements)
references
References 45 publications
2
34
1
Order By: Relevance
“…A few studies found that resting energy expenditure was reduced in patients with narcolepsy [17,28]. However, other studies demonstrated that the BMR did not significantly differ between patients and healthy controls [16,18]. These inconsistent results may be related to the small sample size in these studies, or to differences in patients' ages or disease durations.…”
Section: Changes In Bmrmentioning
confidence: 88%
“…A few studies found that resting energy expenditure was reduced in patients with narcolepsy [17,28]. However, other studies demonstrated that the BMR did not significantly differ between patients and healthy controls [16,18]. These inconsistent results may be related to the small sample size in these studies, or to differences in patients' ages or disease durations.…”
Section: Changes In Bmrmentioning
confidence: 88%
“…When narcoleptics with a BMI < 30 kg/m 2 were studied separately, the BMR and EE were lower than that of BMI-matched controls [29]. Other studies have shown no difference [30].…”
Section: Discussionmentioning
confidence: 99%
“…Orexins affect the wakefulness pattern and physical activity, which are parameters not fully considered in these studies. By extrapolating these data, one might predict that human narcoleptics would have a lower metabolic rate, but that does not seem to be the case (107).…”
Section: Feeding and Metabolismmentioning
confidence: 99%